PENGARUH STORE LAYOUT TERHADAP IMPULSE BUYING DI TOKO BUKU GRAMEDIA ISTANA PLAZA BANDUNG - Heni Rohaeni; Asti Damayanti (Jurusan Akuntansi Politeknik Negeri Bandung, 2018)
Store layout is one of the retail marketing strategy elements named retail mix which can impact the purchasing. The objective of this research is to analyze how the effect of store layout in retail marketing strategy toward impulse buying on Gramedia Books Store products at Istana Plaza Bandung. This research applied quantitative approach with non-probability sampling method and convenience technique. The sample of this research is 100 visitors of Gramedia Books Store at Istana Plaza Bandung. This research used questionnaire as research instrument with 21 questions and analyze with coefficient correlation test, coefficient determination test, and regression test. The result of this research indicate that the store layout have an effect toward impulse buying equal to 58,06% and the residue equal to 41,94% effected by some other factor. The equal of 58,06% show that the store layout has a strong relation toward impulse buying on Gramedia Book Store products at Istana Plaza Bandung. Keywords: Store Layout, Impulse Buying.